2017
DOI: 10.1111/pedi.12514
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced impairment of glucose tolerance: Prevalence among pediatric patients on long-term steroid use in Nigeria

Abstract: Low to moderate doses of oral and inhaled steroids should be used when indicated as they are associated with lesser risk of impairment of glucose tolerance in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated some form of glucose metabolism disorders in adults with chronic steroid use for various conditions, with prevalence between 0.4% and 54%. [18,19] The prevalence has varied across studies and has been difficult to establish because of the variation in diagnostic criteria, length of follow-up, type of immunosuppression, and racial difference. There are few reports about medication-induced diabetes in pediatric patients with NS, although there are some reports on organ transplantation or hematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated some form of glucose metabolism disorders in adults with chronic steroid use for various conditions, with prevalence between 0.4% and 54%. [18,19] The prevalence has varied across studies and has been difficult to establish because of the variation in diagnostic criteria, length of follow-up, type of immunosuppression, and racial difference. There are few reports about medication-induced diabetes in pediatric patients with NS, although there are some reports on organ transplantation or hematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that GCS can impair glucose tolerance, mainly by inducing insulin resistance, and that the effects seem to be dose-dependent [26,27]. In addition, a possible causal role in direct beta-cell dysfunction has been suggested [28].…”
Section: Hy Induced By Gcsmentioning
confidence: 99%
“…In the severe forms of DCS, significant neurological, respiratory and circulatory deficits or failure are frequently involved, and steroids are routinely used due to their potency on inhibiting systemic inflammation, reducing capillary permeability, maintaining cell membrane and reducing tissue edema (Kizer, 1981). However, many studies have shown no significant improvement of DCS when treated with steroids (Dromsk et al, 2003;Montcalm-Smith et al, 2008), and may even worsen the outcome of central nervous system injury due to their adverse effect of elevating blood glucose (Chikani et al, 2017). Hence, there has been a decline in the use of steroids for the treatment of severe DCS as well as other critical diseases due to their adverse effects and uncertainty of outcomes (Dromsk et al, 2003;Felleiter et al, 2012;Gibbison et al, 2017;Walje et al, 2017;Oh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%